Glycans of SARS-CoV-2 Spike Protein in Virus Infection and Antibody Production - Zhao, Xiaohui; Chen, Huan; Wang, Hongliang (Frontiers in Molecular Biosciences, 2021)
Viral protein glycosylation represents a successful strategy employed by the parasite to take advantage of host-cell machinery for modification of its own proteins. The resulting glycans have unneglectable roles in viral infection and immune response. Spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which presents on the surface of matured virion and mediates viral entry into the host, also undergoes extensive glycosylation to shield it from human defense system. It is believed that the ongoing COVID-19 pandemic with more than 90,000,000 infections and 1,900,000 deaths, is partly due to its successful glycosylation strategy. On the other hand, while glycan patches on S protein have been reported to shield the host immune response by masking ‘non-self’ viral peptides with ‘self-glycans’, the epitopes are also important in eliciting neutralizing antibodies. In this review, we will summarize the roles of S protein glycans in mediating virus-receptor interactions, their roles in antibody production as well as indications for vaccine development.